Process optimization of vacuum fried cassava (Manihot esculenta Crantz) chips using response surface methodology - Magtibay, Francis Philip S.
This study aimed to optimize the process parameters of vacuum frying of cassava chips using response surface methodology (RSM). Statistical models that described the effects of temperature 90 110C, time 8 20 min, and loading capacity 10 30 during vacuum frying were generated. The responses in this study were color acceptability, texture acceptability, overall acceptability, L value, a value, bvalue, moisture content and water activity. The response values obtained were fitted with a cubic equation with backward selection by a multiple regression analysis. The optimal conditions for vacuum frying of cassava chips determined were 96.40C temperature, 14.93 min time, and 10.00 loading capacity, with desirability concept of 0.751. This combination of process parameters resulted to an acceptable vacuum fried cassava chips with the desired texture, moisture content 2 d.b. and water activity 0.2. Validation experiments were conducted to measure the predictability of the models and the findings showed that the models accurately predicted the responses.